(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Yeats created a world of his own while other contemporary Englishpoets remained caught in the mire of what we may call the disease of moderncivilization and culture generated by devastating world war. He has a peculiar yeatsian world where he hasdealt with various themes. Yeats wrote a large number of love poems. Theromantic poet exalts and glories love. For him love is a grand and sublime passion. The early works of Yeatscontains a number of romantic love poems. “The Lover Tells the Rose in hisHeart” is a beautiful, intensely emotional and romantic poem. Yeats love poetryis substantial and therefore deserves a separate consideration. Yeats was inlove with Maud Gonne but did not receive her love in return. A kind offrustration, disillusionment is always there in all his poetry. Sometimes hewants to escape from the real world to some other world. “The wonderings ofOisin” is a poem full of romanticism Yeats poem “When you are old” is concernedwith time and beauty Yeats feels a sort of pride because when time will snatchaway beauty from Maud Gonne, beauty for which she is boasting and rejectinghim, she will find that only the poet loved her with a religious zeal: “But oneman loved the pilgrim soul in you.” Yeats feels some satisfaction that even ifbelatedly, she will realize his loves for her, and perhaps will repent so. Yeat’s love poems were nostalgic and autumnal, with a heavy Victorianodour. The recognition of brute physical energy was alien to the early yeats.During the nineties Maud Gonne was the dominating figure in his life.Fascinated by her beauty and her passion, he also founds in her a rather rudemystical belief akin to his own.